Behavioral intention among gen z an analysis of digital banking adaptation factors in Jabodetabek - Zea, Diva Akiela Fahlerie; Halim, Rizal Edy (Journal of Entrepreneurial Economics, 2024)
Background: Many traditional banking arrangements have changed as a result of the financial sector's new technological revolution. One method the company seeks to provide consumers with more value is by delivering digital transformations that are especially designed to match their needs and preferences and that use mobile devices such as cell phones to access banking services. This study aims to examine the effect of performance expectancy and effort expectancy to behavioral intention of adopting digital banking. Method: This study collects data from 243 respondents aged 17 to 27 who live in Jabodetabek area, had experienced to do offline transaction, and have at least one digital bank account. Partial Least Squares Structural Equation Modeling (PLS-SEM) was then used to process the data collected. Findings: The findings of this study shows that shows that effort expectancy has a positive effect on behavioral intention on using digital banking. Meanwhile, performance expectations do not have a significant positive effect on behavioral intention. Conclusion: The results of the research may be used to develop a strategic plan and put recommendations into practice to better understand user intentions to use digital banks.